Proyeksi Pertumbuhan Penduduk Kecamatan Cibinong Dengan Metode Matematik - Herlina, Nina; Kustiawati, Dedek; Liza Halimi, Denia; Mayang Sari, Andita (Rifa'Institute, 2023)
This study examines the growth model with mathematical methods used to obtain information or predict future population growth in Cibinong. In this study, researchers used data we obtained from the Central Bureau of Statistics (BPS) of West Java Province. Data were taken by researchers from the results of the 2010 – 2020 population census. The method used is a mathematical method consisting of arithmetic models, geometric models and exponential models. . Based on the results of the analysis, that large population growth is known by using the Exponential Model. Meanwhile, for the Geometry, Arithmetic model, it shows that population growth continues to occur in the Cibinong area, although it is very small.